Second-order analysis of an imperfect corroded tubular member on a two-parameter elastic foundation. (15th April 2017) - Monsalve-Giraldo, J.S.; Giraldo-Londoño, O.; Colorado-Urrea, G.J.; Dantas, C.M.S.; Aristizabal-Ochoa, J. Dario
Highlights: This paper investigates the stability and second-order behavior of corroded pipes. Corrosion is assumed as a non-uniform loss of wall thickness. The pipe is assumed to rest on a two-parameter elastic foundation. Initial geometric imperfections and different loading conditions are considered. The model agrees with ABAQUS and results found in the technical literature. Abstract: This paper presents a method for the second-order elastic and stability analyses of a corroded tubular member with initial geometric imperfections, resting on a two-parameter elastic foundation. It is assumed that the member is a simply supported Euler–Bernoulli beam-column with a corroded, yet compact cross section. Corrosion is modeled as symmetric loss of wall thickness that varies in magnitude along the member length. Moreover, the member is loaded both axially, transversely and simultaneously subjected to internal and external pressures. Despite all the effects considered herein, this model neglects the effects of thermal loads and torsion, as well as shear and axial deformations along the member. The fourth-order boundary value problem that governs the second-order elastic behavior of the tubular member is solved using the Galerkin method. The proposed method and corresponding equations are used to obtain the second-order transverse deflections, as well as the bending moment and shear force diagrams. This method is also used to estimate the buckling load and compressive strength of the tubular member, which play an important role in the design of tubular structures. The accuracy and effectiveness of the aforementioned formulation are evaluated using four comprehensive examples. The results from the examples demonstrate that the proposed method can be used in the analysis and design of submerged or non-submerged tubular members at a low computational cost.